Antisense oligonucleotides - Daniel R. Scoles; Eric Vallabh Minikel; Stefan M. Pulst (2019)
There are few disease-modifying therapeutics for neurodegenerative diseases, but successes on the development of antisense oligonucleotide (ASO) therapeutics for spinal muscular atrophy and Duchenne muscular dystrophy predict a robust future for ASOs in medicine. Indeed, existing pipelines for the development of ASO therapies for spinocerebellar ataxias, Huntington disease, Alzheimer disease, amyotrophic lateral sclerosis, Parkinson disease, and others, and increased focus by the pharmaceutical industry on ASO development, strengthen the outlook for using ASOs for neurodegenerative diseases. Perhaps the most significant advantage to ASO therapeutics over other small molecule approaches is that acquisition of the target sequence provides immediate knowledge of putative complementary oligonucleotide therapeutics. In this review, we describe the various types of ASOs, how they are used therapeutically, and the present efforts to develop new ASO therapies that will contribute to a forthcoming toolkit for treating multiple neurodegenerative diseases.